Ureas in Organic Synthesis. XII. Syntesis of 2-Amino-5-chlorobenzhydrylureas and their heterocyclization; Russian Journal of Organic Chemistry; Vol. 33, № 4 - Bakibaev A. A. Abdigali Abdimanapovich (1997, 1997)
A synthetic method was developed for hard-to-get biologically active 2-amino-5-chlorobenzhydrylureasbased on reaction of the corresponding benzhydrols with urea in sulfuric acid. The 2-amino-5-chlorobenzhydrylureas were shown to easily undergo on heating cyclization to 1-R-1,2,3,4-tetrahydro-4-phenyl-chloroquinazolin-2-ones.